Physiologically Triggered Digital Cognitive Aid Facilitates Crisis Management in a Simulated Operating Room: A Randomized Controlled Study. Issue 6 (December 2017) - Lipps, Jonathan; Meyers, Lori; Winfield, Scott; Durda, Michael; Yildiz, Vedat; Kushelev, Michael
Abstract : Introduction: Although the benefits of using cognitive aids in anesthesia care have previously been demonstrated, several challenges remain. It must be presented in a timely manner, and providers must be amenable to using the tool once it is available. We hypothesized that anesthesia residents would perform superiorly when presented with a digital cognitive aid (DCogA) that is automatically triggered by a set vital sign aberration. Methods: Thirty anesthesia residents were randomized to either control (with access to hard copy of the cognitive aid) or receive a DCogA projected on their anesthesia information management system with the onset of heart block and associated hypotension. The scenario ended upon commencement of pacing, and the times to interventions were recorded. Results: Fourteen participants were randomized to the control group and 16 to the intervention group DCogA. In the control group, 6 of 14 participants failed to pace, and in the DCogA group, all participants initiated pacing ( P < 0.01). Those in the DCogA group were also faster to pace [260.1 (137.5) s vs. 405.1 (201.8) s, P = 0.03]. Both groups were similar with respect to their knowledge of advanced cardiovascular life support as measured by a pretest ( P = 0.92). Conclusions: We found those participants who were presented with electronic, physiologically triggered cognitive aids were more likely to appropriately treat heart block by initiating transcutaneous pacing. We believe that adoption of a high-functioning anesthesia information management system designed to detect physiologic perturbations and present appropriate decision support tools would lead to safer intraoperative care.